Q. 474.8( 11 Votes )
Solve for x and y
⇒ b2x + a2y = a3b + ab3 …(i)
x + y = 2ab …(ii)
To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.
Lets multiply equation (ii) by a2, so that variable y in both the equations have same coefficient.
Recalling equations (i) & (ii),
b2x + a2y = a3b + ab3
x + y = 2ab [×a2]
⇒ b2x – a2x = - a3b + ab3
⇒ (b2 – a2)x = ab(b2 – a2)
⇒ x = ab
Substitute x = ab in equations (i)/(ii), as per convenience of solving.
Thus, substituting in equation (ii), we get
(ab) + y = 2ab
⇒ y = ab
Hence, we have x = ab and y = ab.
Rate this question :